Behavior of fiber-reinforced polymer-strengthened reinforced concrete beams under static and impact loads - Pham, Thong; Hao, Hong (Multi-Science Publishing Co. Ltd., 2017)
This study investigates the behavior of fiber-reinforced polymer-strengthened reinforced concrete beams under static and impact loads. The experimental program includes six beams tested in static loads and seven beams tested against impact loads. Longitudinal fiber-reinforced polymer strips and fiber-reinforced polymer U-wraps were used to strengthen these beams. The section of four beams was modified to have a curved soffit in order to reduce the stress concentration of fiber-reinforced polymer U-wraps and provide confinement effect on longitudinal fiber-reinforced polymer strips. The experimental results showed that the proposed modification significantly increased the beam capacities as compared to their rectangular counterparts strengthened with the same amount of fiber-reinforced polymer material. In addition, this article also provides explanations and discussions on the phenomenon of shifting of the flexure failure mode under static loads to the shear–flexure failure mode under impact loads of all the beams tested in the study, as well as the proper interpretations of the measured impact forces in the tests. From the experimental results, it is recommended that the impact force and inertial force at the very early stage of an impact event should be used to design the impact resistance.